2019
DOI: 10.1016/j.aquaculture.2019.734260
|View full text |Cite
|
Sign up to set email alerts
|

Ecosystem service framework and typology for an ecosystem approach to aquaculture

Abstract: The ecosystem approach to aquaculture (EAA) considers ecosystem services (ES) important, but does not provide a conceptual framework or a typology to integrate and assess them. To supplement the EAA, a literature review of the ES conceptual framework and ES typologies was combined with selected criteria from the EAA and ES literature. Eight criteria of transition from a conventional approach to aquaculture to the EAA were used as selection criteria to choose a conceptual framework of ES relevant with the EAA. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 52 publications
(78 reference statements)
1
17
0
Order By: Relevance
“…In this context, the use of functional ingredients such as prebiotics or probiotics, which until now have been used mainly in monoculture, could be adapted to future polyculture given the high diversity of taxonomic groups and thus the risk of pathogen transmission. Beyond these tools, the use of sustainability indicators (Valenti et al ., 2018) and evaluation of ecosystem services (CICES, 2018) should be generalised and used to evaluate polyculture systems and help to meet future challenges (Willot et al ., 2019).…”
Section: Limits Of Polyculture Approaches and Future Developmentsmentioning
confidence: 99%
“…In this context, the use of functional ingredients such as prebiotics or probiotics, which until now have been used mainly in monoculture, could be adapted to future polyculture given the high diversity of taxonomic groups and thus the risk of pathogen transmission. Beyond these tools, the use of sustainability indicators (Valenti et al ., 2018) and evaluation of ecosystem services (CICES, 2018) should be generalised and used to evaluate polyculture systems and help to meet future challenges (Willot et al ., 2019).…”
Section: Limits Of Polyculture Approaches and Future Developmentsmentioning
confidence: 99%
“…2019; Willot et al . 2019). Within this context, there is an opportunity to use emergy synthesis as a potential tool to provide this framework (Ortega & Bastianoni 2015).…”
Section: Aspects That Deserve Attention When Applying Emergy Synthesimentioning
confidence: 99%
“…Including ES&D in the revenue or in the production costs has been a challenge for economists and environmental scientists involved with aquaculture sustainability studies (Valenti et al 2018). Although some authors have suggested ways to measure and value ES&D (Table 3), there is a lack of a conceptual framework supporting the identification and linkage of ES&D with different aquaculture systems, as well as its integration with sustainability assessment tools (Kim et al 2017;Alleway et al 2019;Willot et al 2019). Within this context, there is an opportunity to use emergy synthesis as a potential tool to provide this framework (Ortega & Bastianoni 2015).…”
Section: Ecosystem Services and Disservicesmentioning
confidence: 99%
“…Based on the literature review, a conceptual framework of the theoretical relationship between ecosystem services, multifunctionality and diversification of the traditional carp pond aquaculture was developed (Figure 1). Several articles on ecosystem services in aquaculture have recently been published [4,31,32]. However, very few incorporated fish farmers' perceptions of pond ecosystem services [8,25].…”
Section: Introductionmentioning
confidence: 99%